Life Cycle Assessment of Power-to-Syngas: Comparing High Temperature Co-Electrolysis and Steam Methane Reforming - Schreiber, Andrea; Peschel, Andreas; Hentschel, Benjamin; Zapp, Petra (Frontiers in Energy Research, 2020)
To achieve the European Union’s ambitious climate targets, not only the energy system must be transformed, but also other sectors such as industry or transport. Power-to-X (PtX) technologies enable the production of synthetic chemicals and energy carriers using renewable electricity, thus contributing to defossilization of economy. Additionally, they provide storage capacity for renewable energy. Detailed life cycle assessments (LCA) of PtX is required, to prove the environmental advantages to fossil-based benchmark technologies. An emerging PtX technology for syngas production is the high temperature co-electrolysis (HT-co-electrolysis), which produces syngas. Aim of this LCA is the evaluation of syngas production by HT-co-electrolysis at its early stage of development to derive incentives for further research. For comparison, a small-scale steam methane reforming process (SMR) serves as today’s fossil-based benchmark. The required CO2 is obtained via direct air capture. The by-far most important input for the HT-co-electrolysis is electricity. Hence, several future electricity mixes are considered, representing two different climate protection targets (CPT80, CPT95) for the energy system in 2050. For each CPT, an additional distinction is made regarding full load hours, which depend on the availability of renewable energy. The results show lower global warming potential (GWP) and fossil fuel depletion for HT-co-electrolysis compared to SMR if mostly renewable power is used. Exclusively renewable operated HT-co-electrolysis even achieve negative net GWPs in cradle-to-gate LCA without considering syngas use. If HT-co-electrolysis shall operate continuously (8,760 h) additional fossil electricity production is needed. For CPT80, the share of fossil electricity is too high to achieve negative net GWP in contrast to CPT95. Other environmental impacts such as human toxicity, acidification, particulate matter or metal depletion are worse in comparison to SMR. The share of direct air capture on the total environmental impacts is quite noticeable. Main reasons are high electricity and heat demands. Although plant construction contributes to a minor extent to most impact categories, a considerable decrease of cell lifetime due to higher degradation caused by flexible operation, would change that. Nevertheless, flexibility is one of the most important factors to apply PtX for defossilization successfully and reinforce detailed research to understand its impacts.